Związki frazeologiczne z komponentem przestrzennym "su" w ujęciu kognitywnym. Próba analizy na materiale języka włoskiego - Bocian, Edyta (Acta Neophilologica, 2022)
This article aims to demonstrate the basic relationships at the level of spatial relations, in which the primary prepositional meanings translate into figurative language within the phraseological units containing the component su. The author attempts to answer the question as to whether the image schema, indicated as semantically crucial in the interpretation of the polysemy of this preposition, can affect the semantic motivation of the indicated units. The analysis leads to the conclusion that the impact is uneven, and does not apply to all patterns and relationships discussed.